A Study on Characteristics and Comparison of Evaporation Estimation Methods in Bandung - Rusmawan Suwarman; Novitasari Novitasari; I Dewa Gede Agung Junnaedhi (Institute for Research and Community Services (LPPM) ITB, 2021)
This study aims to understand the characteristic of evaporation and to evaluate the evaporation estimation methods to be employed in Bandung by using observation data at three different land cover characteristics sites, namely, densely vegetated area (Baleendah), densely built-up area (Ujung Berung), and mix of buildings and vegetation area (ITB). Observation data used are hourly evaporation, vapour pressure deficit, temperature, relative humidity, wind speed, and radiation. The analysis was done mostly by using statistical methods such as regression analysis and error comparison. The result shows the dominant weather factor affecting the evaporation in ITB and Ujung Berung is vapour pressure deficit, and in Baleendah is solar radiation. The methods of evaporation estimations used in this study are Trabert, Schendel, Turc, and CIMIS-Penman methods. The result shows that the original constant values of those methods are significantly correlated. However, the Schendel is found the most overestimated, and the second is Turc. The best estimated evaporation in Baleendah, ITB, and Ujung Berung is calculated using CIMIS-Penman with one hour lag of radiation, Trabert, and Calibrated Schendel, respectively. The improvement of constant value was applied to Schendel and the result is better than the original constants.